2018
DOI: 10.2169/internalmedicine.1344-18
|View full text |Cite
|
Sign up to set email alerts
|

Is Severe and Long-lasting Linezolid-induced Optic Neuropathy Reversible?

Abstract: Abstract:Linezolid is a useful drug for treating drug-resistant tuberculosis. However, the associated toxicities, especially optic neuritis, are a major obstacle for its long-term use. We recently experienced a case of severe optic and peripheral neuropathy during the treatment of multidrug-resistant tuberculosis. The treatment continued for 12 months despite severe optic and peripheral neuropathy. At eight months after the discontinuation of the drug, the optic neuropathy recovered, but the peripheral neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…19 Persistent irreversible neuropathy has also been reported. 25 A majority of patients with neuropathy in our study also reported gradual relief of symptoms after cessation of linezolid regimen. Consistently with other studies, the median time for elimination of neuropathic symptoms in our study was about 6 months.…”
supporting
confidence: 53%
“…19 Persistent irreversible neuropathy has also been reported. 25 A majority of patients with neuropathy in our study also reported gradual relief of symptoms after cessation of linezolid regimen. Consistently with other studies, the median time for elimination of neuropathic symptoms in our study was about 6 months.…”
supporting
confidence: 53%
“…It is relatively safe when used for a period of fewer than 28 days (16). In the majority of reported cases of neuropathy, the dose was 600 mg once daily, and the length of exposure ranged from 5 to 14 months (8)(9)(10)(11). After conducting a systematic review and meta-analysis of the efficacy and safety of therapy with linezolid-containing regimens in the treatment of drug-resistant tuberculosis, Zhang X et al determined that neurotoxicity with peripheral neuropathy occurs in 30% of patients who had received doses <or equal to 600 mg/day for 4-6 months (7,16).…”
Section: Discussionmentioning
confidence: 99%
“…Linezolid-induced optic neuropathy is nearly reversible, but the exact duration of symptom resolution following drug discontinuation is unknown. The majority of reported cases of optic neuropathy resolved within 1-3 months of drug discontinuation (8)(9)(10)(11). However, the presence of other systemic illnesses can impede optic neuropathy recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Data from [5,9–11,15–23,32,34,39 ▪ ,40 ▪ ,41–57,58 ▪ ,59–66]. MRSA, methicillin-resistant staphylococcus aureus; TB, tuberculosis.…”
Section: Characteristics Of Linezolid-associated Optic Neuropathymentioning
confidence: 99%
“…Visual field defects are the second most common clinical finding in patients with LON and occur in 51 of 55 (92.7%) of patients followed by dyschromatopsia in 45 of 49 patients (91.8%) (Table 1). The time to recovery has been reported in the literature anywhere from 4 days to 6 months after cessation of linezolid with an average time of 3 months (Table 1) [9,11,[15][16][17].…”
Section: Characteristics Of Linezolid-associated Optic Neuropathymentioning
confidence: 99%